An Investigation of Profiles for Plate Cams with Vertical In-line Roller Followers - M. R. M., Rejab; M. M., Noor; K., Kadirgama; M. M., Rahman; Z., Ahmad@Manap; M. S. M., Sani; R., Daud (2009)
This paper presents an evaluation of graphical method and experimental work for determining plate cam profiles. Both methods are accurate for obtaining points on a cam with vertical roller followers. The coordinates of the centre of the follower are required at small increments of the cam angle. It can be easily programmed and depend only on the follower coordinates and not the follower type. A comparison on motion analysis has been made to determine the percentage error occurred in both methods. From result between graphical and experimental methods, the different of the follower displacement calculated and shows the small value of displacement occur among them where less than 5 %.